2021
DOI: 10.1111/jfpp.16002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modified atmosphere packaging on physicochemical properties of fresh‐cut ‘Deveci’ pears

Abstract: This study aimed at determining the respiration rate of fresh-cut 'Deveci' pears and studying the effects of modified atmosphere packaging (MAP) on its quality. Respiration rate decreased with decreasing O 2 level and it was determined as 1.04 ml O 2 /kg/hr or 1.16 ml CO 2 /kg/hr, under 4% O 2 +5% CO 2 gaseous environment at 4°C. Michaelis-Menten with no inhibition was the best model to fit the respiration data. MAP under 2.15% O 2 +8.70% CO 2 equilibrium atmosphere resulted in a lower total color change, a*-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Since MAP technology retains water via packaging, it reduces water loss during transpiration [ 29 ]. Similar results were obtained by Oguz-Korkut et al [ 30 ] for fresh-cut ‘ Deveci ’ pears. MAP packaging retained a high relative humidity at 4 °C and 4% O 2 + 5% CO 2 , maintaining the firmness and water of the sliced pears.…”
Section: Resultssupporting
confidence: 91%
“…Since MAP technology retains water via packaging, it reduces water loss during transpiration [ 29 ]. Similar results were obtained by Oguz-Korkut et al [ 30 ] for fresh-cut ‘ Deveci ’ pears. MAP packaging retained a high relative humidity at 4 °C and 4% O 2 + 5% CO 2 , maintaining the firmness and water of the sliced pears.…”
Section: Resultssupporting
confidence: 91%
“…A study on blueberries revealed that the content of all organic acids and soluble sugars decreased significantly throughout the refrigeration process, regardless of the processing method (Pinto et al, 2020). However, in a study of fresh‐cut pears, there was also a slight decrease in pH; overall, MAP treatment (4% O 2 + 5% CO 2 ) did not affect quality characteristics such as TSS, pH, and titratable acids during the storage period (Oguz‐Korkut et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…MAS is a technique in which the internal atmosphere of the product is modified and maintained to such a level of O 2 and CO 2 gas concentrations which are optimal for prolonging the shelf life of fresh produce by maintaining its natural quality and freshness. Researchers like Leila et al, 2021 and Oguz‐Korkut et al, 2021 have worked on the application of modified atmosphere technique for increasing the shelf life and maintaining the freshness of fresh produce for longer period of time. They reported that the shelf life of a pre‐treated fresh‐cut salad lettuce and fresh‐cut “Deveci” pears can be effectively increased by MAS technique, respectively.…”
Section: Introductionmentioning
confidence: 99%